DRAWING UP FRAUD PRACTICES AT XYZ STATE UNIVERSITY AUTOBIOGRAPHY OF EXPENDITURE TREASURER ASSISTANT - Rakhmatullah, Hans Wakhida; Irianto, Gugus; Achsin, M. (The International Journal of Accounting and Business Society, 2018)
The objective of this study is to disclose fraud practices in State University XYZ based on the author’s experience in working as expenditure treasurer assistant. This qualitative interpretive study uses autobiographical approach. The result shows that fraud practices occur in work units in State University XYZ. The causes are (a) poor internal control in the university, (b) negligence and collusion committed by certain parties, (c) performance pressure that make employees do anything it takes to improve their performance, and (d) pressure from superiors to finish tasks regardless using inappropriate ways. Accountability report of public sector units does not care about appropriateness but document completeness and validity. The report can pass auditor’s surveillance if it is complete and valid.Keywords: fraud, autobiography, accountability report